Fermentation Characteristics of Lactococcus lactis subsp. lactis Isolated From Naturally Fermented Dairy Products and Screening of Potential Starter Isolates - Li, Weicheng; Ren, Min; Duo, Lana; Li, Jing; Wang, Shuai; Sun, Yaru; Li, Min; Ren, Weiyi; Hou, Qiangchuan; Yu, Jie; Sun, Zhihong; Sun, Tiansong (Frontiers in Microbiology, 2020)
It is well known that consumers are keen to try fermented milk products with different flavors and starter cultures are important in determining the resulting fermented dairy products. Here, we present the phenome of 227 Lactococcus lactis subsp. lactis isolates from traditionally-fermented dairy products and the selection of those producing the malt aroma which is popular in China. Large-scale phenotyping revealed significant technological diversity in fermentation characteristics amongst the isolates including variation in fermentation time, viscosity, water holding capacity and free amino nitrogen production. The 16 isolates with the best fermentation characteristics were compared, in a sensory evaluation, with the commercial starter Chr. Hansen R-704 as excellent fermentation characteristics to identify potential starter isolates and find the isolate which can product good flavors. From these, and from SPME-GC-MS analysis, we identified IMAU11823 and IMAU11919 as producing 3-methyl butanal and 3-methyl-2-butanone which contribute to the malt aroma. This study expands the characterization of L. lactis subsp. lactis phenotypic dataset and technological diversity and identified isolates with potential culture starter in the fermentation industry.